Pengaruh Pemberian Hypnoanalgesia Pada Nyeri Post Operasi Fraktur Di Rumah Sakit Karima Utama Surakarta - Prasetyo, Joko Waneng, Okti Sri Purwanti. S.Kep., M.Kep., Ns. Sp.Kep.M.B (2016)
Fracture is a broken bone or disruotion of bone tissue caused by direct or indirect trauma. One way to rstore the fracture that is by way of rekognisi or done surgery the patient will experience pain. Pain management treatment there are 2 techniques by pharmacology and non pharmacology. One of the techniques of pain management on non pharmacological is hypnoanalgesia. Hypnoanalgesia is the definition of the power of the subconscious ability in directing, the depiction on delusion, and attention. Hypnoanalgesia is also a working system to reduce sensitivity to pain by using the approach to hypnosis. One of the keys of the hypnoanalgesia is that person want to do relaxation hypnoanalgesia actions to reduce the pain and was able to fully concentrate focus or during the following session hypnoanalgesia. Particularly in patients post operatif of fracture, there after a patients undergoes surgery things main thing is patients will experience pain. The pain should immediateiydo action a pain reliever so as not to disturb the psychological patients during the healing process to take place. The goal in this research is to know the influence of hypnoanalgesia on pain post surgery fractures at the hospital Karima Utama Surakarta. The design research of pre-experiment with design reaserch pre test post test control group design. The sample in research are patients post fracture surgery at the hospital karima utama Surakarta. The technique of sampling in this research is the technique of Accidential Sampling. Instrument in this study using a sheet of observation in the form of pain scale Numberic rating scale. Statistical test used in this study is the Wilcoxon test rank test. Wilcoxon test rank test results obtained by the group's treatment of the value of significance (p-value) 0.004 and results from the control group values the significance (p-value) 1.000. the conclusion is there is the influence of hypnoanalgesia on pain post surgery fractures at the hospital karima utama Surakarta.